Bond behavior of stainless steel components and concrete: A review. (October 2022) - Wang, Jizhong; Xiao, Fangduo; Yang, Junlong
Abstract: To alleviate the detrimental effect of harsh environments on the durability of steel–concrete composite structures, the use of stainless steel (SS) instead of conventional carbon steel (CS) in concrete structures has been gaining increasing attention recently. Due to the different microstructures and mechanical properties between SS and CS, the bond behavior of SS components to concrete may vary significantly compared to CS counterparts, leading to the incapability of current design codes and existing bond-slip models for stainless steel–concrete components. Thus, this paper comprehensively summarizes the bond behavior of various stainless steel components and concrete based on an extensive review of published literature, including stainless steel bars, tubes and other components. It reveals that bond mechanisms and bond-slip responses heavily depend on the types of stainless steel components, and the effects of various influenced factors are also discussed in detail for each stainless steel component. Based on the test database assembled from existing studies, two strength models are proposed to predict the bond strength of stainless steel bars and tubes to concrete respectively, while practical design suggestions are also developed for the remaining stainless steel components, which may provide some guidance for the subsequent research.